7(2+x)+6x=

Simple and best practice solution for 7(2+x)+6x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(2+x)+6x= equation:


Simplifying
7(2 + x) + 6x = 0
(2 * 7 + x * 7) + 6x = 0
(14 + 7x) + 6x = 0

Combine like terms: 7x + 6x = 13x
14 + 13x = 0

Solving
14 + 13x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-14' to each side of the equation.
14 + -14 + 13x = 0 + -14

Combine like terms: 14 + -14 = 0
0 + 13x = 0 + -14
13x = 0 + -14

Combine like terms: 0 + -14 = -14
13x = -14

Divide each side by '13'.
x = -1.076923077

Simplifying
x = -1.076923077

See similar equations:

| -3x-3=-3x+-3 | | y=-200x+1880 | | 3+48=-6 | | x^2-51x+144=0 | | 8(c+7)-4x=3x+15c+x | | 7a^2+-2+-13a=0 | | 6x-9-15x+5-x-11= | | -82+6x+x=72 | | x-3/3=x+4/4 | | 60-10=5x | | 3x+17=63 | | 63x=63 | | 13+x=-4 | | 0.01(5-0.2x)=0.75+0.198x | | 4z=52 | | 4c-2=7c+77 | | 16x+4-110=3x+11 | | y=x^3-6x^2+11x-6 | | 4(d+3)+7d=0 | | 3x+x+12=27 | | 4+2x+3=34 | | y=450x-3320 | | -2(x+1)=-3(2x+2) | | .5(y+4)=x | | -7y+8-6y-13= | | 22=18-0.25x | | 3(x+2)-4=2x | | 12x^2-10x-42=0 | | 10/4=z-8/16 | | x=.5(y+4) | | 4(w^2)-22w+10=0 | | -40=2n |

Equations solver categories